The African refugee crisis – challenging the notion of burden-sharing in Africa - Nyirongo, Rachael (Department of Public Law, 2023)
For decades, Africa has faced a large number of refugees and this has been rapidly growing since 2010. Although there has been another recent spike in refugees on the continent, the cause of refugees today is largely due to the increase in conflict on the continent, whilst in earlier years this was due to colonialism. The rise of intra and interstate conflicts shows a correlation with the increase in the number of refugees. Africa has the largest population of refugees in the world, according to the Population Division of the United Nations Department of Economic and Social Affairs (DESA). In 2019, Africa was hosting 26 million migrants and 7 million refugees, including asylum seekers. The top five African refugee-generating countries all have ongoing conflicts or are in a state of dealing with the conflicts through peace agreements. In addition to displacement as a result of conflict, African countries have complex issues that contribute to the rise in these numbers and these issues range from economic struggles, social security deficiencies, political tensions and displacement as a result of climate change. The distribution of refugees is not even as most refugees choose to stay in neighbouring countries, and resettlement numbers have been dropping in recent years. As conflicts are the main cause of refugees on the continent, East African countries bear the biggest burden of refugees as many countries in the region are dealing with severe insecurities. This large influx of refugees in that region causes a genuine concern about whether they can sustainably provide for them and protect their rights. Most of these countries are developing countries with a low Human Development Index (HDI) and are already struggling to provide for their locals. This thesis aims to look at three of the top four African refugee-hosting countries which are located in East Africa. It will look into what responsibilities these hosting states have concerning protecting the basic rights and providing the basic needs of the refugees, to what extent they are able to provide for the refugees and what gaps are they unable to fulfil with their own efforts. After determining a need for more burden-sharing practices on the continent, it will analyse what practices are already taking place and what more can be done by African states and the international community as a whole.